Studi Performa Mesin Pencacah Polimer Komposit Berbasis Uji Laboratorium - Sianturi, Danial Jack Marbis; Tumangger, Theo Fredrik; Aldori, Yopan Rahmad; Iswandi, Iswandi; Umroh, Bobby (CV. IRA PUBLISHING, 2025)
Polymers are the result of monomer polymerization with a lower density than metals but a much smaller elastic modulus, making them less rigid and strongly affected by temperature. This study evaluates the performance of a laboratory-scale crushing machine for polypropylene blended with activated carbon at varying compositions. The machine employed carbon steel rotary blades driven by a 1 HP electric motor through a gearbox transmission. Results showed average crushing times of 3.5–4 minutes/kg. Pure polypropylene produced a 72% fine fraction, while adding 10% activated carbon reduced it to 65%. Crushing efficiency remained above 85%, demonstrating stable performance and feasibility for composite material applications.